TDP-43 Potentiates Alpha-synuclein Toxicity to Dopaminergic Neurons in Transgenic Mice - Tian Tian, Cao Huang, Jianbin Tong, Ming Yang, Hongxia Zhou, Xu-Gang Xia (International Journal of Biological Sciences, 2011)
TDP-43 and α-synuclein are two disease proteins involved in a wide range of neurodegenerative diseases. While TDP-43 proteinopathy is considered a pathologic hallmark of sporadic amyotrophic lateral sclerosis and frontotemporal lobe degeneration, α-synuclein is a major component of Lewy body characteristic of Parkinson's disease. Intriguingly, TDP-43 proteinopathy also coexists with Lewy body and with synucleinopathy in certain disease conditions. Here we reported the effects of TDP-43 on α-synuclein neurotoxicity in transgenic mice. Overexpression of mutant TDP-43 (M337V substitution) in mice caused early death in transgenic founders, but overexpression of normal TDP-43 only induced a moderate loss of cortical neurons in the transgenic mice at advanced ages. Interestingly, concomitant overexpression of normal TDP-43 and mutant α-synuclein caused a more severe loss of dopaminergic neurons in the double transgenic mice as compared to single-gene transgenic mice. TDP-43 potentiated α-synuclein toxicity to dopaminergic neurons in living animals. Our finding provides in vivo evidence suggesting that disease proteins such as TDP-43 and α-synuclein may play a synergistic role in disease induction in neurodegenerative diseases.